Gambaran Krisis Respon Komunitas LGBTI di Kota Makassar - Muhammad Arsyad Rahman; Dinda Nur Maharani; Nur Panasita; Nabila Salsabilah; Vica Regina Bintari (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2023)
This research aims to obtain in-depth information about the motives behind the persecution cases of the LGBTI community in Makassar, as well as how the LGBTI community can survive in a society that rejects it. This research method uses ethnographic methods about why and how identity acceptance, group organizing, violence in relationships with partners, legality of partner status, diversity of identity construction, support system responses, and health behaviors are influenced by ethnographic methods, trying to answer what LGBTI communities and support systems do, to whom they do certain actions, and how people, LGBTI communities, and support systems deal with persecution cases as part of actions that violate the law. The results showed that the community is hampered in the acceptance of identity but makes efforts to organize the group; the source of violence comes from socio-economic crush; legally, there is no recognition of the state and citizens; the construction of diversity is not a serious problem; the response of the support system is a vacuum and is still in search of a formula, and community health behavior has not included safe sex. The conclusion of the research is that the LGBTI community is in a state of anxiety, worry, and fear because of the potential for persecution, physical violence, and verbal violence at any time, while the support system, such as the community empowerment office, social service office, health office, village, community association, neighborhood association, religious leaders, community leaders, and community organizations, have not made real efforts such as dialogue or formal meetings for the security and safety of the lives of LGBTI communities.